AKTIVITAS PROGRAM SOCIAL INVESTMENT PT. CHEVRON PACIFC INDONESIA DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT PADA BIDANG EKONOMI DI MINAS, PROVINSI RIAU - Putra, Aditya Agus; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Corporate social responsibility (CSR) is basically a necessity for corporations to be able to interact with local communities. Corporate needs to adapt in order to get social benefits from its relationship with the local community in the form of trust. In the implementation of CSR required a culture based on ethics that is adaptive. This study aims to determine the activity of PT Chevron Pacific Indonesia's social investment program in improving community empowerment in the economic field in Minas, Riau Province. What are the programs that have been created and implemented by the company and the constraints found in the implementation.This study used qualitative research methods. Research subjects consisted of 8 informants selected through purposive technique. Data collection is done through observation, interview and documentation. To test the validity of the data writer used the method of extension of participation and triangulation.The result of this research shows that the activity of Chevron Riau Social Investment Program runs well from the forms of programs run by the company through PRISMA, among others are fishery, handicraft, cassava farming, animal husbandry, and integrated agricultural community. This program is intended for helping to develop communities that are close to the company's concessions while encouraging regional economic growth. PRISMA program proved to improve the quality of the economy and change the mindset of the community to become more productive, improve the welfare of the community around the company's operational area, foster the beneficiary community groups to be independent so as to raise the spirit of group members to develop their business, and grow new business groups.Keyword : Corporate Social Responbility